1978
DOI: 10.4315/0362-028x-41.9.726
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Factors in Color Evaluation of Purees, Pastes, and Granular Food Specimens

Abstract: The standard measurement situation for color involves a specimen which is flat, uniform in color, and thin. For measurements of colors of many food products, instruments which give reliable and reproducible results when applied to the flat, uniform and thin traditional specimens are unreliable. This is because specimens of foodstuffs come in a variety of shapes, sizes and translucencies. The unreliability of instrument measurements can be shown to be related to instrument differences in geometry and to: (a) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…shown that instrumentally measured redness is more highly correlated to carotenoid concentration when colour is measured in a measuring cell than when measured directly on the fillet surface (Schmidt & Cuthbert 1969), and that an even better correlation may be achieved by taking measurements on homogenized samples (Johnsen & Wathne 1990). Some of the variation that remains unexplained by the regression models we have used may, thus, be the result of heterogeneity on the surface and in the matrix of the fillet (Hunter & Christie 1978). These irregularities would be expected to be reduced or eliminated by homogenization.…”
Section: Discussionmentioning
confidence: 99%
“…shown that instrumentally measured redness is more highly correlated to carotenoid concentration when colour is measured in a measuring cell than when measured directly on the fillet surface (Schmidt & Cuthbert 1969), and that an even better correlation may be achieved by taking measurements on homogenized samples (Johnsen & Wathne 1990). Some of the variation that remains unexplained by the regression models we have used may, thus, be the result of heterogeneity on the surface and in the matrix of the fillet (Hunter & Christie 1978). These irregularities would be expected to be reduced or eliminated by homogenization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ability to remember colours is limited (Hunter 1975). and the surroundings may also in-fluence the perception of the colour (Hunter & Christie 1978). It is therefore important to standardize the viewing conditions and to use standardized colours (Boiton (It a/.…”
Section: Visual Colour Evaluationmentioning
confidence: 99%